PRAKTEK PENDIDIKAN JARAK JAUH DI UNIVERSITAS TERBUKA INDONESIA - Masruroh, Feriana (EDUTECH, 2020)
Distance education is certainly still considered not as effective as face-to-face education or direct learning. This review article aims to describe the practice and application of distance education carried out at the Indonesian Open University from 2010 to 2020. The results have shown that from year to year along with the development of technology, media and methods of distance education at the Indonesian Open University continue to be developed. In addition, students' perceptions of distance education also tend to be positive. However, face-to-face meetings must still be held. Pendidikan jarak jauh tentunya masih dianggap tidak seefektif pendidikan tatap muka atau pembelajaran langsung. Artikel telaah ini bertujuan untuk mendeskripsikan praktik dan penerapan pendidikan jarak jauh yang dilakukan di Universitas Terbuka Indonesia dari tahun 2010 hingga 2020.  Hasil dari telah  menunjukkan bahwa dari tahun ketahun seiring perkembangan teknologi, media dan metode pendidikan jarak jauh di Universitas Terbuka Indonesia terus dikembangkan. Selain itu, persepsi mahasiswa mengenai pendidikan jarak jauh juga cenderung positif. Namun, tetap harus diadakan pertemuan tatap muka.